A comparative analysis of legislated and modified Baltic Sea trawl codends for simultaneously improving the size selection of cod (Gadus morhua) and plaice (Pleuronectes platessa) - Wienbeck, Harald; Herrmann, Bent; Feekings, Jordan P.; Stepputtis, Daniel; Moderhak, Waldemar (Fisheries Research, 2014)
Five modified trawl codends were assessed for their utility in simultaneously improving the size selectivity of cod (Gadus morhua) and plaice (Pleuronectes platessa) in the Baltic Sea. The modifications included refining the selective performance of the current Bacoma codend by increasing the mesh size of the lower panel from 109 mm double twine to 129 mm single twine and increasing the mesh size in the upper square mesh panel from 132 to 147 mm, and also making the lower panel the same design as the upper panel; i.e. a full square mesh codend. These three experimental designs were tested in conjunction with the currently legislated codends; Bacoma and T90. The most favourable selective properties with regard to simultaneously improving the selectivity for round and flatfish, considering the current minimum landing sizes (MLS) for cod (38 cm) and plaice (25 cm) in the Baltic Sea and the fish population size structures during the sea trials, were found to be the T90 codend and the Bacoma codend with a modified lower panel. For the T90 codend, the selection parameters (L50 and SR) were 43.4 and 6.7 cm for cod, and 24.7 and 2.1 cm for plaice. The selection parameters for the most effective modified Bacoma codend were 41.1 and 8.3 cm for cod and 25.2 and 3.9 cm for plaice